Tumor biobanks in translational medicine - Botti, Gerardo (BioMed Central, 2012)
The concept of tissue banking as a “bio-repository” aimed to collection, storing and distribution of human biological material and clinical information, is emerging as a successful strategy to support clinical and translational research. In particular, Tumor Biobanks represent a key resource for diagnosis, research and experimental therapies, especially for those correlated to clinical application of a new type of medicine known as “intelligent drugs”. Biobanks are not “spontaneous” collections, but they needs an institutional organization, basically a research unit, whose effectiveness and quality can be guaranteed only if it is carefully organized according to precise and shared rules.